Epidemiology and genetic characterization of porcine reproductive and respiratory syndrome virus in Fujian Province, China, from 2023 to 2024 - Long-Bin Kang; Long-Bin Kang; Qiu-Yong Chen; Qiu-Yong Chen; Bing He; Bing He; Ren-Jie Wu; Ren-Jie Wu; Jing-Li Qiu; Jing-Li Qiu; Ru-Jing Chen; Ru-Jing Chen; et al. (Frontiers in Veterinary Science)
Porcine Reproductive and Respiratory Syndrome (PRRS) is associated with reproductive disorders, respiratory diseases and slower growth rates. PRRSV mutation and recombination lead to the emergence and spread of novel strains, which brings challenges and complexity to clinical prevention and control. However, the epidemical characterization of PRRSV in Fujian is limited. In this study, 262 suspected PRRSV samples from 87 pig farms in Fujian Province, from 2023 to 2024 were collected to monitor the prevalence of PRRSV. Through RT-PCR detection and sequencing of the Nsp2 hypervariable region, ORF5, and ORF7 genes, an analysis of their genetic variation was conducted. The results revealed that the overall prevalence rate of PRRSV was 16.79% (44/262), PRRSV-1 and PRRSV-2 genotypes were co-prevalent in Fujian. Phylogenetic analysis of ORF5 gene identified 37 PRRSV strains, categorizing 1 as PRRSV-1, 36 as PRRSV-2, including 17 strains of NADC30-like subtype (45.95%), 9 strains of lineage 8 (24.32%), 7 strains of lineage 3 (18.92%), 2 strains of NADC34-like subtype (5.41%), and 1 strain of lineage 5 (2.70%). The main way of amino acid change of GP5 is a mutation, and some strains have a deletion. These changes are mainly observed in T cell, B cell epitope region, signal peptide region, and transmembrane region. The above results indicated that NADC30-like was the dominant circulating strain, followed by the HP-PRRSV strain in the farm. Moreover, genetic evolution analysis of the Nsp2 gene showed that the pattern of amino acid deletion between different lineages no longer seems to be applicable as a molecular marker for each lineage, and genetic diversity and recombination were commonly observed. Noteworthy, the identification of a novel independent subtype from the isolated strains indicates that the ORF7 gene also has genetic evolution, which requires us to pay attention to the genetic relationship of ORF7 between the wild strain and the vaccine strain. This study offers crucial insights into the evolutionary dynamics of PRRSV, thus providing a solid foundation for further research into PRRSV epidemiology and control strategies.